Pengaruh Corporate Risk, Profitabilitas terhadap Tax Avoidance pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia - Barus, Irene Sukma Lestari; Winiasih, Shelma Alya; Sugianto, Paulus; Mulyati, Yati (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to determine how the influence of Corporate Risk, profitability, on Tax Avoidance on property and Real Estate companies listed on the Indonesia Stock Exchange in 2019-2023. This research is motivated by the unstable condition of the company, which sometimes has an increase and a decrease in the variable Corporate Risk and profitability. The method of data collection used in this study is the documentation method. The sample determination technique used in this study is a purposive sampling technique. The number of samples in this study amounted to 92 property and Real Estate companies listed on the Indonesia Stock Exchange in 2019-2023. The method of analysis used in this study is regression analysis of panel data at the significance level of 5%. The Program used in analyzing data is Eviews. The results of the study partially show that Corporate Risk (X1) has no effect on Tax Avoidance in property and Real Estate companies listed on the Indonesia Stock Exchange in 2019-2023. Profitability (X2) affects Tax Avoidance in property and Real Estate companies listed on the Indonesia Stock Exchange in 2019-2023, while simultaneously showing that Corporate Risk and profitability affect Tax Avoidance in property and Real Estate companies listed on the Indonesia Stock Exchange in 2019-2023.